Kebutuhan Pengembangan Media Unyil Berbasis Proyek Bermuatan Kreatif untuk Pembelajaran Menulis Teks Anekdot Jenjang SMA/MA - Putri, Novi Auliana; Haryadi, Haryadi; Baehaqie, Imam (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The aim of this research is (1) to describe the needs analysis for the development of project-based Unyil (Literacy Listening Unit) media with creative content for learning to write anecdotal texts for class learning to write anecdotal texts in SMA/MA class X before carrying out development at the product testing stage. This research method is descriptive qualitative. Data collection techniques include observation, interviews, distribution of development needs questionnaires, and documentation. Questionnaires were distributed to 107 students, then interviews were conducted with student representatives and Indonesian language teachers at SMA N 1 Mejobo, MA NU Assalam, and MA Daarusy Syifa. The data obtained was analyzed using descriptive analysis. The results of the research show that the development of creative project-based Unyil learning media is needed in the learning process of writing anecdotal texts. The learning media for writing anecdotal texts using the project-based and creatively charged Unyil (Literacy Listening Unit) media is expected to make students more interactive, creative, and able to express ideas in writing contemporary and useful anecdotal texts. Apart from that, the Unyil media prototype developed contains discussions with animated videos, images, text, quizzes and motivation that are interesting and fun so that students are able to produce the desired projects well and successfully.